Translingual online identities in the global South: The construction of local 'gang cultures' in the social media spaces of Balkan and South Korean artists. (December 2022) - Milak, Eldin; Tankosić, Ana
Highlights: Translingual practice bridges the online-offline nexus. Artists in the Global South freely relocalize linguistic and semiotic resources. Identities and communities emerge and are shared through translingual practice. Translingual identities in Southern artists' social media produce the 'gang culture' Indiscriminate relocalization raises questions of authenticity and ownership online.